The concept of Individuality in Friedrich Meinecke’s Early Work - Rodrigues da Cunha, Marcelo Durão (Revista de Teoria da História, 2023)
This article investigates the centrality of the concept of individuality in the young Friedrich Meinecke’s theory of history, positing it as a fundamental element shaping Meinecke’s historical conception. To elucidate this position, an analysis is conducted to discern the significance attributed to the principium individuationis at two critical junctures in Meinecke’s early intellectual development: firstly, in his response to the positivist assault on the German historical school, and secondly, in his endeavor to reconceptualize the underpinnings of a revitalized history of ideas between the late 1800s and the initial decade of the twentieth century. By expounding upon these aspects and contextualizing the intellectual evolution in which these ideas emerged, it is argued that the concept of individuality functioned as a theoretical refuge against what Meinecke perceived as the doctrinaire nature of worldviews incompatible with notions of freedom and spontaneity — principles he considered intrinsic to the historical mode of thought.